Tourism and the Bogotá brand: An associative study from the perspective of foreign visitors - Marroquín-Ciendúa, Fernando; Garcia Garcia, Alberto Luis; Sánchez Cid, Manuel (Street Art & Urban Creativity, 2025)
The development of a city brand is structured through a synergistic process that involves and promotes socioeconomic, creative, local, and national factors. In addition, they must be the basis for positioning both among residents and among potential visitors as tourists or investors. The present study aimed to identify the perceptions towards the city of Bogotá by foreign visitors and possible relationships with age and gender, in line with the concept of city brand. A quantitative, cross-sectional, descriptive, and associative study was carried out through surveys of 500 foreigners who visited the city of Bogotá in 2023. General perceptions and significant associations were observed between demographics and factors related to the elements that make up the concept of city brand. Results are discussed and recommendations are made, specifying limitations and considerations for future studies on city brand